Five Years Melioidosis Registry Data from 2011-2015 in Pahang, Malaysia: A Retrospective Study - Hin, How Soon; Zainulabid, Ummu Afeera; Ibrahim, Mohamad Shafiq Mohamad; Mahmud, Fatihah; Chiu, Lim Bee; Singh, Kiren Kaur Bhajan; Chee, Loh Thian; Fong, Ken Voon; Sulong, Mohd Rahim (Bangladesh Journal of Infectious Diseases, 2023)
Background: Melioidosis cases were conducted throughout the state of Pahang, Malaysia, from 2000 to 2004, and found that there were high annual incidences and mortality rates among melioidosis patients. A series of programs on medical education has since been introduced throughout Pahang, and a registry has been created to track the effects. Objective: We established and investigated the melioidosis registry with the aim of improving the state's melioidosis management Methodology: This comprehensive review of the 239 confirmed melioidosis cases from 1st January 2011 to 31st December 2015 was performed to trace the cultures from all microbiology laboratories in Pahang. Comparisons were made between these cases and previous records retrieved from the registry. Information was verified from the patient’s case note when necessary. Results: The patients, aged from 1 to 84 years, were predominantly males (78.2%), Malays (82.0%), and had a median age of 51 years. The most common predisposing factor present in 165 (69.0%) patients was diabetes, while the most common clinical presentation observed in 109(45.6%) patients was pneumonia. With outcomes that were known within 209 patients, 106(50.7%) of them did not survive, and while the other 103(51.6%) were fully discharged. Patients who were fully discharged received appropriate antibiotics for both intensive and eradication therapies. Twenty patients (8.4%) had culture-confirmed relapses. Conclusion: Despite improvements in patient management, especially in treatment involving antibiotics, mortality rates remained high. Collectively, these research have found important relationships and insights that contribute for further management of the illness at the state level. Bangladesh Journal of Infectious Diseases, June 2022;9(1):7-14